(untitled) (Research, Society and Development, 2020)
This article aims to reflect on the pedagogical work carried out by the school library of a municipal school in Fortaleza, State of Ceará, Brazil during remote classes. This is a qualitative study, which consisted of a case study. For data collection, we used the following instruments: questionnaire and interview. We initially carried out a mapping in four schools with the teachers who work in the library. And one of the teachers affirmed her participation in remote classes. Therefore, we directed the investigation to the pedagogical work developed by the teacher to understand how her interventions were happening in the sense of stimulating the students’ reading training. The main results pointed out that the educator who works in this library tried to carry out a work to encourage reading within the conditions of remote classes in this period of pandemic in order to bring students closer to the reading practices that were already carried out in the classroom with the support of library. To this end, it sought to maintain weekly meetings with each class, the reception with music or other resources were also present and there was always the proposition of reading from storytelling, production of authorial videos and interactions with students. Therefore, we conclude the relevance of the function of the school library for the reading training of students and we reiterate the need for more investment in these spaces and the importance of valuing reading practices that are planned collectively and are part of the continuing education of teachers.